Answer:
Point P is in between points F and G.
Now, here we do not have the actual locations of F and G, so i will answer this in a general way.
Suppose that F is located at 0 and G is located at some value A.
Then the distance FG = A - 0 = A.
Now, the distance between F and P is:
Distance = (1/4)*FG = A/4
Then the location of P is equal to the location of F plus A/4
P = 0 + A/4
Now, writing this in a more general way:
P = F + FG/4
The coordinate of point P is represented by the expression 0.75f + 0.25g. This is found by taking the coordinate F and adding 1/4 of the distance FG, which is represented by the coordinates g - f.
In order to find the coordinate of point P, we first need to understand the problem properly. You are given that point P is located between points F and G, and the distance from F to P is one-fourth the distance from F to G. If we represent these points on a number line, suppose the coordinate of F is 'f' and that of G is 'g'.
Then, the distance from F to G is 'g - f'. Given that FP = 1/4 FG, the coordinate of point P, p, is 'f' plus 1/4 of 'g - f'. That is:
p = f + 1/4(g - f) = f + 0.25g - 0.25f = 0.75f + 0.25g.
This expression gives the coordinate of P in terms of the coordinates of F and G.
#SPJ3
Answer:
it is circle
Step-by-step explanation:
just got it correct
Answer:
the answer is circle
Step-by-step explanation:
i got it right on edge2020 :)
Answer:
x = 2
Step-by-step explanation:
Step 1: Convert to math
5x + 1 = 3x + 5
Step 2: Solve for x
Step 3: Check
Plug in x to verify it's a solution.
5(2) + 1 = 3(2) + 5
10 + 1 = 6 + 5
11 = 11
Answer:
2
Step-by-step explanation:
there are 5 x's and 1 positive one of the left side, and 3 x's and five positive one's on the right side. when you put this into an equation, you get:
5x+1 = 3x+5
the first step to solving the equation is to subtract 3x from both sides:
5x+1 -3x = 3x+5 -3x
2x+1 = 5
next, subtract 1 from both sides:
2x+1 -1 = 5 -1
2x=4
finally, divide both sides by 2:
2x ÷2 = 4 ÷2
x=2
and the answer is: 2
1) 6b-9
2)6(b-p)
3)6-bp
4)6bp
y = 8x + 23
How many shirts would you have to purchase for the total cost to be the same at both companies?
Answer:
5 shirts
Step-by-step explanation:
Y=12x+3 equation 1
y=8x+23 equation 2
12x+3=8x+23 substituting y value will cause equations to equal
4x=20
x=5 shirts
check answer
y=12x+3
y=12(5)+3
y=60+3
y=63
y=8x+23
y=8(5)+23
y=40+23
y=63